Connections in the semiholonomic frame bundle of order r - Navickis, Kazimeras (Lietuvos matematikos rinkinys, 1999)
In this article we define the canonical forms on the principal bundle of semiholonomic frames of order r, give structure equations for these forms and determine the connection of order r.